Efektivitas Penerapan Mindful Learning Sebagai Strategi Terhadap Konsentrasi Siswa Kelas V Sdn Cipageran Mandiri 3 - Winarti, Rosi; Faramadina, Nabilah Fitria; Mirella, Riska (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
Mindful learning is an approach to students in the learning process that emphasizes transforming a concept into a new form by combining the ideas they possess. This mindful approach contributes to emotional social development because during the learning process, students consciously manage and accept various feelings they experience. The application of mindful learning as a concentration strategy for fifth-grade students at SDN Cipageran Mandiri 3 cannot be effectively implemented, due to distractions in the classroom that undermine students' concentration during the learning process. By adding STOP in the classroom, it will enhance students' control over their concentration. The results of the research using Likert scale on the control and experimental classes, as well as the N-Gain Test for Pretest and Posttest on students' concentration, prove that the results are considered low, thus the mindful learning approach did not proceed as expected. This approach poses a challenge for an educator to try implementing the mindful learning approach at SDN Cipageran Mandiri 3 by establishing a common agreement before the learning process begins so that this approach can function as intended and comply with the applicable curriculum.